Microwave switched gas discharges and their application for the CO2 laser - März, Martin; Brand, Hans (Archiv fuer Elektrotechnik, 1996)
This paper is dealing with a new method of controlling gas discharges by the means of microwave energy. The technique called microwave/d.c. hybrid excitation combines the simple energy storage in the case of d.c. excitation with the wide tracking range of r.f. excited discharges especially with respect to pulse frequency and power density. Shifting the energy storage to a high voltage circuit allows the use of very inexpensive microwave sources such as magnetrons for microwave cooking, while no power switch is necessary at the high voltage side. The feasibility of microwave/d.c. excited CO2 lasers is demonstrated with several examples. It is shown that these lasers can be continuously operated between a cw mode and a pulsed mode with high peak power exaltation, in which the operating mode can be dynamicaly changed within a few millisecond